Online Food Poisoning Educational Intervention: Can It Be an Effective Medium to Improve Consumer’s Knowledge, Attitude and Risk Perception on Food Poisoning Prevention? - Masyita Mamot; Nurul Azmawati Mohamed; Shalinawati Ramli; Rukman Awang Hamat; Mohd Dzulkhairi Mohd Rani; Malina Osman; Zamberi Sekawi (UPM Press, 2024)
Indexed by Scopus